Phage therapy: An old concept with new perspectives - Izabela Durbas, Grzegorz Machnik (Journal of Applied Pharmaceutical Science, 2022)
The ever-increasing bacterial resistance to antibiotics and the growing number of severe, hard-to-treat infections have driven international studies into a race to develop alternative, less conventional methods of treatment. One such antibacterial strategy has been around for a relatively long time, just recently resparking scientific interest: it is called phage therapy. In the fight against multidrug-resistant bacterial infections, this method employs one of the most abundant organisms on the planet Earth—bacteriophages—a type of intriguing, spiderlike viruses which infect bacteria. The newest research in the field of phage therapy and its applications in medicine suggests that this method indeed has the potential to become an alternative form of treatment for patients suffering from various diseases, as it turns out, not only bacterial infections. However, there is still much to be learnt about phage biology, its impact on the human body, and its interactions with bacteria. Nonetheless, in the face of a significant global health threat, the time has come to reexamine this almost-century-old medical strategy.
Keywords: Bacteriophages, phage therapy, drug resistance, antibacterial agents, bacterial infections